Humic acid in the production of ornamental lawn plugs and shading levels in the development of Carpet grass - Watanabe, Beatriz; Tavares, Armando Reis; Costa, João Victor; Nascimento, Matheus Vinicios Leal do; Zabotto, Alessandro Reinaldo; Godoy, Leandro José Grava de; Bôas, Roberto Lyra Villas; Santos, Patrick Luan Ferreira dos (Ornamental Horticulture, 2025)
The use of biostimulants has been studied as a technology that improves the cultivation of plant species and could therefore be an option for producing turfgrass seedlings. Furthermore, Carpet grass is recommended for semi-shaded locations, however there are few studies that indicate the best shading percentage for the species. Thus, this work aimed to evaluate humic acid in the production of ornamental lawns plugs and shading levels in the development of Carpet grass. The experiment was divided into two parts, the first being the production of seedlings (30 days) of Emerald grass, DiscoveryTM Bermudagrass, Carpet grass and Bahiagrass with application of humic acid. On the second part the development of Carpet grass was evaluated at 4 levels of luminosity (full sun and shading of 30%, 50%, and 80%) in 28 days. The evaluations carried out were: green color index (GCI), normalized difference vegetation index (NDVI), root length and dry mass of the seedlings for the first part. And for the second part: GCI, SPAD (Soil Plant Analysis Development), NDVI, visual aspect, coverage rate, lawn height and dry mass of clippings. It was observed that the use of a humic acid- based biostimulant is recommended in the production of plugs for ornamental lawns, and the best results on Carpet grass, where, the shading level up to 50% for this species is recommended in analyses of up to 28 days.